Sistem Informasi Akuntansi Arus Kas Berbasis WEB Pada CV. Simpang Ampek Jaya Kota Pontianak - Herliani, Puji (Jurnal Sistem Informasi Akuntansi, 2021)
CV. Simpang Ampek Jaya Pontianak is a company engaged in the culinary field of Padang cuisine. In the process of Cash Flow on CV. Simpang Ampek Jaya Pontianak still uses a manual system in recording data and managing cash inflows, outflows and recapitulation reports using book notes. The methodology used is the Extreme Programming method. The results of the following research are in the form of a cash flow application system design that is able to manage incoming and outgoing cash data. This web-based Cash Flow application was created using the PHP (Hypertext Preprocessor) programming language as a tool and run the software, Visual Studio Code text editor and its open source code, MySQL as the database, Php MyAdmin as the database editor, and Xampp version 7.2.2 as the database editor. the web server. And the outputs generated in this web-based application include cash inflow report data, cash out report data, and cash flow report data. With this web-based cash flow application, it is expected to be able to manage incoming and outgoing cash more effectively and efficiently and the application system is now more conducive.